The anti-fungal and anti-oxidant properties of polyphenols extracted from the resurrection plant, Myrothamnus flabellifolia - Shibambo, Segopotjo Linah (Department of Molecular and Cell Biology, 2014)
Includes bibliographical references (leaves 84-94).